Euthanasia in veterinary medicine: Review - Dallari Júnior, José Alfredo (Pubvet, 2024)
The word “euthanasia” has a greek origin, basically meaning “good death”. The technique is applied to humans and animals and, in Veterinary Medicine, it must be elected by the person responsible for the pet and who is guided by the veterinarian. The procedure must be performed by a professional or qualified person under their supervision and carried out quickly, avoiding as much as possible, the patient suffering. This article’s goal is to present the topic, deepen concepts such as mystanasia, orthothanasia and dysthanasia, as well as discuss the responsibility of the veterinarian throughout the process, from supporting the animal’s tutor in the decision for palliative care to, finally, carrying out the procedure in an ethical manner.